Predictors of perceived stigmatization in patients with psoriasis. (1st March 2017) - van Beugen, S.; van Middendorp, H.; Ferwerda, M.; Smit, J.V.; Zeeuwen‐Franssen, M.E.J.; Kroft, E.B.M.; de Jong, E.M.G.J.; Donders, A.R.T.; van de Kerkhof, P.C.M.; Evers, A.W.M.
Summary: Background: The physical appearance of psoriasis can be cosmetically disfiguring, resulting in a substantial social burden for patients. An important aspect of this burden is the experience of stigmatization. While stigmatization is known to be disabling and stressful for patients, little is known about its correlates, and effective interventions are lacking. Objectives: To examine predictor variables for perceived stigmatization in psoriasis. Methods: Questionnaires were administered to 514 patients with psoriasis in a cross‐sectional study. Zero‐order correlation and multiple‐regression analyses were conducted including sociodemographic, disease‐related, personality, illness cognitions and social support predictor variables. Results: Stigmatization was experienced by 73% of patients to some degree, and correlated with all five categories of predictor variables. In multiple‐regression analyses, stigmatization was associated with higher impact on daily life; lower education; higher disease visibility, severity and duration; higher levels of social inhibition; having a type D personality; and not having a partner. Conclusions: The results indicate that perceived stigmatization is common in psoriasis, and can be predicted by sociodemographic, disease‐related and personality variables. These predictor variables provide indications of which patients are especially vulnerable regarding perceived stigmatization, which might be used in treatment.